Emerging Market Bond Spreads and Sovereign Credit Ratings : Reconciling Market Views with Economic Fundamentals - Sy, Amadou (IMF Working Papers; Working Paper, 2001)
This paper uses a panel data estimation of a simple univariate model of sovereign spreads on ratings to analyze statistically significant deviations from the estimated relationship. We find evidence of an asymmetric adjustment of spreads and ratings when such deviations are significant. In addition, the paper illustrates how significant disagreements between market and rating agencies' views can be used as a signal that further technical and sovereign analysis is warranted. For instance, we find that spreads were "excessively low" for most emerging markets before the Asian crisis. More recently, spreads were "excessively high" for a number of emerging markets.